Risk control methods in a hotel operation - Bednarska, Marlena (Economics and Business Review, 2004)
Risk is an immanent characteristic of all economic processes. Since a defensive approach to business and avoidance of risk at all costs may result in the loss of potential benefits and a waste of resources, companies should implement methods of professional diagnostics and active control of risk. The aim of the paper is to present in a systematic way the methods of risk control in a company and analyse their relevance to the hotel industry. After a brief introduction concerning objectives and stages of risk management procedure, physical and financial methods of risk control are presented. Given the attributes of tourism demand and the specific features of the lodging industry, techniques of demand risk control are analysed. Special attention is paid to such actions as joining a renowned hotel chain through franchising, outsourcing services, investing in weather derivatives, signing charter or quota contracts. (original abstract)